Comparisons of choroidal nevus measurements obtained using 10- and 20-MHz ultrasound and spectral domain optical coherence tomography - Martins,Maíra de França (2017)
ABSTRACT Purpose: To compare measurements of lesions clinically diagnosed as choroidal nevi using spectral domain optical coherence tomography (SD-OCT) and 10- and 20-MHz ultrasound (US). Methods: This prospective study, which was conducted between May 2011 and December 2011, evaluated eyes diagnosed with choroidal nevus via photographic documentation using 10- or 20-MHz A- and B-mode US (experienced examiner using both the transpalpebral technique and direct contact) or SD-OCT in the enhanced depth imaging mode (performed by a different examiner blinded to the US results). Anteroposterior (AP) and transverse (T) US sections corresponded to sections adjusted perpendicularly on SD-OCT. Results: We evaluated 14 eyes from 12 patients (six males, mean patient age= 64.5 years) diagnosed with choroidal nevus. The choroidal nevi of all samples had a melanocytic profile. Moreover, eight nevi were located at the equator, five nevi were located in the posterior pole (peripapillary in one sample), and one nevus shifted from the equator to the periphery. On SD-OCT, the maximum measurable dimension was 9 mm. The lesions in the posterior pole were easier to evaluate, and image acquisition of lesions located more peripherally was possible depending on patient cooperation. The accurate assessment of height was difficult. Baseline dimensions on 10- and 20-MHz US were larger than those determined via OCT. No significant differences in height were observed between US and SD-OCT. All parameters were statistically similar between 10- and 20-MHz US measurements. Conclusions: No significant difference in the AP and T diameters was observed between 10- and 20-MHz US measurements; however, these measurements (AP and T) were significantly higher than those obtained using OCT. No significant differences in height were observed among the techniques adopted.